Kecerdasan Emosional Dalam Pendidikan Islam - Mar'atus Sa'idah (ILUMINASI: Journal of Research in Education, 2023)
Emotional intelligence is an intelligence that must be possessed by every individual. By having emotional intelligence, a person is able to encourage himself and survive in the face of frustration, set moods, empathize, and pray. In addition, someone who has emotional intelligence will also be able to live a life oriented only to divinity, not desire. Emotional intelligence is carried out according to intelligence and spiritual intelligence. Spiritual intelligence can be obtained from Islamic education. In addition, Islamic education learning materials also contain teachings about emotional intelligence.